Development and characterization of 10 microsatellite markers in the Cape horseshoe bat, Rhinolophus capensis (Chiroptera, Rhinolophidae) and cross-amplification in southern African Rhinolophus species. (December 2015) - Nesi, Nicolas; Jacobs, David; Feldheim, Kevin; Bishop, Jacqueline
Abstract Background The Cape horseshoe bat, Rhinolophus capensis, is endemic to the Cape region of South Africa. Coalescent analysis of mitochondrial DNA sequence data suggests extensive historical gene flow between populations despite strong geographic variation of their echolocation call phenotype. Nevertheless the fine-scale genetic structure and evolutionary ecology ofR. capensis remains poorly understood. Here we describe the development of 10 novel polymorphic microsatellite loci to investigate of the dispersal ecology ofR. capensis and to facilitate taxonomic studies ofRhinolophus species in southern Africa. Findings We report 10 microsatellite primer pairs that consistently amplify scorable and polymorphic loci across 12 African rhinolophid species. Initial analysis of two populations ofR. capensis from South Africa revealed moderate to high levels of allelic variation with 4–14 alleles per locus and observed heterozygosities of 0.450–0.900. No evidence of linkage disequilibrium was observed and eight of the loci showed no departure from Hardy–Weinberg equilibrium. Cross-species utility of these markers revealed consistently amplifiable polymorphic loci in eleven additional rhinolophid species. Conclusions The cross-amplification success of the microsatellites developed here provides a cost-effective set of population genetic marker for the study of rhinolophid evolutionary ecology and conservation in southern Africa.